Scar Island - Gemeinhart, Dan (Scholastic Inc., 2018)
The Slabhenge Reformatory for Troubled Boys is a decaying fortress on a remote island, inhabited only by the fifteen boys sentenced to live there and the adults hired to supervise them. It's also twelve-year-old Jonathan Grisby's home for the next ten weeks, and he accepts the punishment he feels he deserves. When a lightning bolt strikes, killing every adult at the reformatory, the boys are suddenly left to fend for themselves. They are enjoying their freedom until another storm strikes, leaving the boys in danger of dying themselves, and forcing Jonathan to face his past in order to save himself and the others.